2017
DOI: 10.1016/j.jcms.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of measurements used to quantify cranial asymmetry in deformational plagiocephaly

Abstract: We recommend using OCLR as the primary measurement, although PCAI and wAS may also be useful in monitoring cranial asymmetry. The threshold of relative asymmetry required for a deformation to appear clinically significant is not affected by the child's age, and DD has no additional utility in monitoring DP compared to using only OCLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Our findings showed that the incidences of plagiocephaly and brachycephaly among preterm infants in Chongqing were significantly higher than those among local term infants (51.1%/43, 85.1%/76%). Compared to internationally reported rates in infants, i.e., 3.9–57.2% (plagiocephaly), 16–48% (brachycephaly), and 21–88% (dolichocephaly), the incidence of dolichocephaly in preterm infants was similar to that in local full-term infants (3.2% vs 3.0%) [12, 20, 24, 30]. The incidence of plagiocephaly in premature infants in this study is high.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Our findings showed that the incidences of plagiocephaly and brachycephaly among preterm infants in Chongqing were significantly higher than those among local term infants (51.1%/43, 85.1%/76%). Compared to internationally reported rates in infants, i.e., 3.9–57.2% (plagiocephaly), 16–48% (brachycephaly), and 21–88% (dolichocephaly), the incidence of dolichocephaly in preterm infants was similar to that in local full-term infants (3.2% vs 3.0%) [12, 20, 24, 30]. The incidence of plagiocephaly in premature infants in this study is high.…”
Section: Discussionsupporting
confidence: 45%
“…With the infant facing the examiner, the examiner held the infant’s head in the center. According to Wilbrand’s standardized scheme [19], we proceeded as follows: Measurements were performed according to a standard protocol determined previously [20]. The following parameters were obtained: cranial circumference, cranial length (glabella[g]–opisthocranion[op]), cranial width (eurion [eu]–eurion [eu]), and transcranial diagonals A and B (frontotemporale[ft]–lambdoid[ld]) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of DP was based on OCLR, with 104% as the cut-off value for DP, which has been described as the most optimal and clinically relevant cut-off point [4,25]. The severity of DP was also categorized based on OCLR: OCLR 104–107.9% indicates mild; OCLR 108–111.9% indicates moderate; and OCLR ≥ 112% indicates severe DP [5,7].…”
Section: Methodsmentioning
confidence: 99%
“…To identify cranial asymmetry and to determine DP, the Oblique Cranial Length Ratio (OCLR) was calculated from the 3D image, and the cut-off point for DP was set at OCLR ≥ 104% as has been described in the context of our earlier study [10,37]. To illustrate location of the TMJ complex, the ear-offset (EO) was calculated as the difference between the right and left tragion along the z-axis.…”
Section: Cranial Asymmetrymentioning
confidence: 99%